Plataformas blockchain para ejecutar contratos inteligentes, un acercamiento empresarial y gubernamental (2021)
The concept of blockchain is gaining more relevance day by day as it is becoming more and more necessary to draw up documents that illustrate the operation of this disruptive technology, since the primary and secondary literature regarding this issue is still very limited. In the following article, different technological platforms where blockchain can be applied will be explained, uncovering their positive and negative aspects. Additionally, use cases in each of these platforms will be shown, at business and governmental levels, so that the reader can have a better approach of the benefit in applying this technology. Finally, the challenges that must be taken into account when implementing this technology will be analyzed.